2019
DOI: 10.4236/jhrss.2019.72014
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality: How Do Racial and Gender Differences Influence the Incomes in US

Abstract: Income inequality is a serious social economic issue in many countries. The issue is deteriorated due to the complex social environment and demographic composition in the Unites States. This study focuses on the racial and gender factors which influence workers' income. And the easy-qualified year of schooling and working-year are chosen as the other two factors. Basing on the Ordinary Least Square (OLS) analysis, the selected factors are qualified to understand their influence degree in income inequality. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, Race has been considered carrying a stronger effect on annual income increment than Sex. Liu et al ( 2019 ) indicated that as the number of work years increases, the gap of income increment attributable by Race was significantly larger than that by Sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Race has been considered carrying a stronger effect on annual income increment than Sex. Liu et al ( 2019 ) indicated that as the number of work years increases, the gap of income increment attributable by Race was significantly larger than that by Sex.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has also observed that the income gap is more associated with Race than Sex. We have proposed that the stronger effect of Race on the Income gap as compared to Sex, might be attributable to its stronger effect on recruitment procedure and annual income increment (Baert, 2018 ; Liu et al, 2019 ; McCarthy and Cheng, 2018 ; Skaggs and Bridges, 2013 ). Policymakers are encouraged to pay more attention to any inherent socio-economic obstacles to achieving greater urban sustainability, including sex and racial-driven income inequality.…”
Section: Discussionmentioning
confidence: 99%
“…In Interaction Effect result, it can be seen that women earn more than men regardless of the type of insurance they invest in. This may be because women receive more from their investment in education than men (Liu, Yang, & Wang, 2019). And the increase in years of education has led to higher earnings for women (Table 3).…”
Section: Interaction Effect Modelmentioning
confidence: 99%